KELAYAKAN MEDIA POSTER SUB MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Peronika Peronika; Syamswisna Syamswisna; Andi Besse Tenriawaru (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to measure the relevance of poster as the result of inventory and to identify the types of Nepenthes which took place in the forest protection area of mount Pejapa in Landak regency. This is a quantitative research with descriptive method. The sample was taken in a path of zig-zag line which was 5 meters to the left and 5 meters to the right. Purposive sampling was used to determine the research sample. Based on the research, it was found that there were 4 types of Nepenthes such as Nepenthes ampullaria Jack, Nepenthes mirabilis (Lour.) Druce, Nepenthes gracilis Korth and Nepenthes tomoriana. The result of this study was implemented in the form of poster media. Media poster need to be revised before being used for learning media. The posters media was examined by two lecturers of biology education study program of FKIP Untan and three biology teachers of grade X in three different schools in Landak district. Based on the assessment of the validators, the poster was valid with the CVI (Content Validity Index) score was 0.91 and feasible to be used as a learning media in the sub material of Indonesian biodiversity.